2014
DOI: 10.1007/s10658-014-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and virulence of Italian strains of Fusarium oxysporum isolated from Eustoma grandiflorum

Abstract: Twenty-seven isolates of Fusarium oxysporum f. sp. eustomae obtained from diseased Eustoma grandiflorum (lisianthus) plants in north Italy, showing typical fusarium wilt symptoms, were studied for genetic diversity, pathogenicity, and vegetative compatibility (VC). The strains were examined for differences in the nucleotide sequence of translation elongation factor 1-α (tef) and two endopolygalacturonase genes (pg1 and pg5). The phylogenetic analysis performed on the isolates enabled the identification of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Arya & Jain 1962 Gordon 1965, Armstrong & Armstrong 1968, 1981, Booth 1971 eustomae 1985aBertoldo et al 2015 fabae Yu & Fang 1948Gordon 1965, Armstrong & Arm-Mbofung et al 2007, O'Donnell et al 2009, Srinivasan strong 1968, 1981, Booth 1971 Armstrong & Armstrong 1968, 1981, Katan & Di Primo 1999, Kim et al 2001, Nagarajan et al 2004, Hirano Booth 1971Nagarajan et al 2006& Arie 2009, O'Donnell et al 2009, Chakrabarti et al 2011, Fang et al 2013…”
Section: Eucalyptimentioning
confidence: 99%
See 1 more Smart Citation
“…Arya & Jain 1962 Gordon 1965, Armstrong & Armstrong 1968, 1981, Booth 1971 eustomae 1985aBertoldo et al 2015 fabae Yu & Fang 1948Gordon 1965, Armstrong & Arm-Mbofung et al 2007, O'Donnell et al 2009, Srinivasan strong 1968, 1981, Booth 1971 Armstrong & Armstrong 1968, 1981, Katan & Di Primo 1999, Kim et al 2001, Nagarajan et al 2004, Hirano Booth 1971Nagarajan et al 2006& Arie 2009, O'Donnell et al 2009, Chakrabarti et al 2011, Fang et al 2013…”
Section: Eucalyptimentioning
confidence: 99%
“…1940, Baayen et al 1997, Hirano & Arie 2009, O'Donnell et al 2009, Fusarium oxysporum f. sp. barbati Kistler et al 1998, Katan Poli et al 2013, Bertoldo et al 2015, Pinaria et al W.C. Snyder, Phytopathology 31: 1056, Katan & Di Primo 2015, Koyyappurath et al 2016, Taylor et al 2016 Sands et al 1997Summerell et al 2010Sands et al 1997, Kistler Sands et al 1997, Lievens et al 2009b, O'Donnell et al 1998, Katan 1999 Katan & Di Primo 1999…”
Section: Introductionmentioning
confidence: 99%
“…However, the phytopathogenic strains cause destructive vascular wilt disease and often limit the production of economically important crops (Servin et al, 2015, Shahzad et al, 2017). The species of Fo cause wilt disease in more than 150 hosts and range with specific formae speciales (Bertoldo et al, 2015). Asha et al, 2011, Nirmaladevi et al, 2016 reported Fusarium oxysporum Schlectend.…”
Section: Introductionmentioning
confidence: 99%
“…However, Fusarium wilt disease on lisianthus, caused primarily by Fusarium oxysporum f. sp. eustomae , has become the most important threat to its production in China, Italy and Japan (Bertoldo, Gilardi, Spadaro, Gullino, & Garibaldi, ). Dazomet fumigation and various RSD treatments incorporated with different organic substrates were carried out on a soil planted continuously with lisianthus for 4 years.…”
Section: Introductionmentioning
confidence: 99%